At skabe sociale relationer ud fra Badehotellet - Philipsen, Heidi; Pilegaard, Nathali (Aktualitet - Litteratur, kultur og medier, 2021)
In this article we study fan culture and activities of viewers in relation to one of the most popular, contemporary Danish tv series: Badehotellet. More specifically, we reflect upon fan practices in a particular digital Facebook group. This is an underdeveloped research field in Danish media studies. Based on reception analysis and observations of Facebook followers’ digital communication, we highlight why and how so many followers are motivated to interact with a fictional universe of a series and how this relates to a participatory culture. The activities in the Facebook group illustrate how followers are able to express and share their enthusiasm towards the story world. This leads us to reflect on the significant ways in which a fan group on Facebook facilitates a sense of belonging to a ‘club’, due to pertinent social functions.